Environmental Reactions of Air-Quality Protection on Eco-Friendly Iron-Based Catalysts - Greta Galloni, Melissa (2020)
A series of iron functionalized hydroxyapatite (Fe/HAP) samples with different metal loading (2 < wt.% Fe < 13) was prepared by a flash ionic exchange procedure from iron(III) nitrate as precursor and tested in some environmental air-quality protection reactions such as the catalytic reduction of NOx by NH3 (NH3-SCR), catalytic oxidation of NH3 (NH3-SCO) and catalytic N2O decomposition. The catalytic performances of the Fe/HAP catalysts were determined under flow conditions as a function of temperature and using reactant concentrations typical of polluting gaseous emissions from industrial vents. Physico-chemical characterization with various techniques of study (UV-DR and Mössbauer spectroscopies, NH3 titration, N2-physisorption, and XRPD analyses) provided valuable information on Fe-speciation, acidity, morphology, and structure of the samples. In general, highly dispersed Fe3+ centers were the predominant species, irrespective of Fe-loading, while just low percentage (≤15%) of FexOy nanoclusters (2 < size/nm < 4) was detected on the samples. As expected, the differences in iron concentration produced a diversified effect of both catalyst properties and catalytic activity, comprising the conversion and selectivity profiles, different for each reaction considered. The obtained results indicate a good potentiality for the eco-friendly Fe-catalysts for some environmental reactions of air protection.